Asia-Pacific regional security assessment 2020 key developments and trends (An IISS strategic dossier, 2020)
The Asia-Pacific Regional Security Assessment provides insight into key regional strategic, geopolitical, economic, military and security topics. Among the topics explored are: the deteriorating USChina relationship and great-power competition; US alliances and security partnerships; the collapse of the Intermediate-range Nuclear Forces Treaty; diplomatic gridlock on the Korean Peninsula; Japan's role in Indo-Pacific security; the breakdown in Japan-South Korea relations; Indonesian policy towards the South China Sea; Australia's defence and security outlook; the European security role in Asia. Authors include leading regional analysts and academics Douglas Barrie, William Choong, Aaron Connelly, Andrew Davies, Michael Elleman, Bonnie S. Glaser, Euan Graham, Christopher W. Hughes, Meia Nouwens, Brendan Taylor and William Tow.